Prognosis of premenopausal women with low-risk endometrial cancer but elevated CA125 levels - Song, Jeong Min; Aiob, Ala; Kim, Kidong; Lee, Kwang Beom; Kang, Sokbom; Lee, Chae Hyeong; Kim, Se Ik; Kim, Nam Kyeong; Jeong, Dae Hoon (Frontiers in Oncology, 2025)
IntroductionWomen with low-risk endometrial cancer, as defined by the Korean Gynecologic Oncology Group (KGOG) criteria, have a low risk of lymph node metastasis and an excellent prognosis without lymphadenectomy. However, it is unclear whether lymphadenectomy should be performed in premenopausal women who meet the KGOG criteria other than elevated cancer antigen 125 (CA125) levels, because the CA125 level can be elevated by benign conditions. We investigated the patterns of metastasis and recurrence to assess the value of lymphadenectomy in this population.MethodsPremenopausal women with endometrial cancer meeting the KGOG criteria, except for those with elevated CA125 levels, were eligible. The characteristics of the eligible women were collected from seven institutes in the Republic of Korea by reviewing their medical records. Recurrence-free survival (RFS) was estimated using the Kaplan–Meier method and compared using the log-rank test.ResultsSeventy-three patients were included. Of 62 women who underwent lymphadenectomy, only two (3.2%) had lymph node metastasis. Eighteen women (24.7%) received adjuvant therapy. At a median follow-up of 59 months, the 5-year RFS was 88.8%. Five women (7%) experienced recurrence, two had lymph node recurrence, and three had non-nodal recurrence. RFS was similar between the women who did and did not undergo lymphadenectomy (P=0.737).ConclusionPremenopausal women who had elevated CA125 levels but met all other KGOG criteria showed a low risk of lymph node metastasis and recurrence as well as a good prognosis. Therefore, lymphadenectomy can be omitted in this population.